2009
DOI: 10.1155/2009/615162
|View full text |Cite
|
Sign up to set email alerts
|

A New Genetic Algorithm Methodology for Design Optimization of Truss Structures: Bipopulation-Based Genetic Algorithm with Enhanced Interval Search

Abstract: A new genetic algorithm (GA) methodology, Bipopulation-Based Genetic Algorithm with Enhanced Interval Search (BGAwEIS), is introduced and used to optimize the design of truss structures with various complexities. The results of BGAwEIS are compared with those obtained by the sequential genetic algorithm (SGA) utilizing a single population, a multipopulation-based genetic algorithm (MPGA) proposed for this study and other existing approaches presented in literature. This study has two goals: outlining BGAwEIS's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…One comparison of quantity of structural analysis made indicates that there is no defined pattern to the behavior of the different methodologies. If the quantity of analysis made for GA from reference (4) and MCGA are compared, it is observed that the MCGA executed 6100 additional analysis for example 2 and 5200 less analysis for example 1.…”
Section: Example 2: Spatial Trussing Of 72 Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…One comparison of quantity of structural analysis made indicates that there is no defined pattern to the behavior of the different methodologies. If the quantity of analysis made for GA from reference (4) and MCGA are compared, it is observed that the MCGA executed 6100 additional analysis for example 2 and 5200 less analysis for example 1.…”
Section: Example 2: Spatial Trussing Of 72 Elementsmentioning
confidence: 99%
“…The solution to the optimization problem requires the selection of a numerical technique capable of solving the current problem, in this case being the metaheuristics a group of optimization algorithms that has good performance (3)(4)(5)(6)(7). The metaheuristic is an approximate optimization algorithm used in the efficient determination of "adequate" solutions of difficult and complex problems in science and engineering, but it cannot guaranty an optimal solution (8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the estimation of the distribution is obtained, two parents are selected to generate new individuals, transferring the allele of each locus to the offspring in those places where the parents are equal and applying the estimated distribution to determine the alleles in those places where the parents have different values. Other similar techniques have been proposed by Varnamkhasti et al [45] and the one reported by Talaslioglu [46]. In the former, a new crossover operator and probability selection technique are proposed based on the population diversity using a fuzzy logic controller, whereas in the latter a bipopulation-based genetic algorithm with enhanced interval search is introduced.…”
Section: Introductionmentioning
confidence: 97%
“…The engineering problems related to structural design comprehend a wide number of situations: trussed systems optimization in both two-dimensional and three-dimensional (Coello and Cristiansen, 2000;Huang and Wang, 2008;Mroginski et al, 2009;Talaslioglu, 2009;Thein and Liu, 2012;Torii et al, 2012), topology analysis of plane frames structures (Stromberg et al, 2012), design of composite structural sections (Lopez et al, 2009), micromechanics optimization (Huang et al, 2011), performance of thermodynamic machines (Ahmadi et al, 2016;Sadatsakkak et al, 2015), fiber reinforced polymeric (Cai and Aref, 2015), among others.…”
Section: Introductionmentioning
confidence: 99%